A first-principles study of He, Xe, Kr and O incorporation in thorium carbide - Perez Daroca, Diego Raul (2015)
Thorium-based materials are currently being investigated in relation with their potential utilization in Generation-IV reactors as nuclear fuels. Understanding the incorporation of fission products and oxygen is very important to predict the behavior of nuclear fuels. A first approach to this goal is the study of the incorporation energies and stability of these elements in the material. By means of first-principles calculations within the framework of density functional theory, we calculate the incorporation energies of He, Xe, Kr and O atoms in Th and C vacancy sites, in tetrahedral interstitials and in Schottky defects along the 〈111〉 and 〈100〉 directions. We also analyze atomic displacements, volume modifications and Bader charges. This kind of results for ThC, to the best authors' knowledge, have not been obtained previously, neither experimentally, nor theoretically. This should deal as a starting point towards the study of the complex behavior of fission products in irradiated ThC.